Culinary Tourism as A Place and Product Branding. Case Study: Batu Jamus Rubber Plantation in Karanganyar, Central of Java - Erni Setyowati; Anggana Fitri Satwikasari (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
Rubber plantation of Batujamus, the largest plantation in Central Java Province and Tourism region of Sukuh Temple in Karanganyar regency, Central Java Province is taken as a case to focus discussion on the meaning of